Smallholder farmers’ willingness to pay for improved forage seeds: The case of eastern Zone of Tigray, Ethiopia - Emuru, D. (Haramaya University, 2015)
The objective of this study was to estimate farmers’ WTP for improved forage seeds and to identify the determinants of farmers’ WTP for improved forage seeds in eastern zone of Tigray, Ethiopia. The data were collected from Atsbi-Womberta and Kilte-Awlaelo districts in “December 2014” from 120 sample household heads for each forage type for the time period January to December 2014. Bivariate Probit model was used, and come up with 64.17%, 55.83% and 65% willing respondents to pay for the improved forages seeds of alfalfa, elephant grass and vetch respectively. The bivariate probit econometric model results of determinants revealed education level, livestock holding, access to credit, initial bid and follow up bids as the significate determining factors of the WTP for improved forage seed. The model have also predicted the mean willingness to pay for each forage seed types, and it is estimated to be 334.53 ETB/kg, 0.30 ETB/30 cm and 38.20 ETB/kg for the improved forage seeds of alfalfa, elephant grass cutting and vetch respectively. Based on the model result for better establishment of the seed business, better financial credit access is recommended to make households capable of using improved forages and to produce market based improved forage seeds. Besides it would be easy for farmers to inter into the forage seed business if improved species of livestock are introduced to the study area that could be complementary with the need to increase livestock holding through creating better credit services for groups or individuals who would like to join the livestock business. While introducing these practices, formal and informal learning strategies such as trainings and experiences need to be included as package of modern livestock husbandry, so that the demand will be created and farmers will be more likely willing to pay for the improved forage seeds. In addition, for entrepreneurs who would like to invest on the improved forage seed production it is recommended to start supply the seeds with equivalent to the mean WTP premium prices elicited on this study for each forage seed types with the consideration of market inflation on the time of production season of the area, so that every household farmer would be indifferent between buying the seeds to support their livestock production and producing it.